An analytical approach for frequency modulated thermal wave imaging for testing and evaluation of glass fiber reinforced polymers. (4th March 2021) - Rani, Anju; Mulaveesala, Ravibabu; Kher, Vansha
Abstract: Frequency modulated thermal wave imaging (FMTWI) has been considered as one of the promising non-destructive testing and evaluation approach due to its merits such as economical, safe, fast, sensitive and high depth resolvability. The present work provides a novel analytical solution for FMTWI using one-dimensional heat conduction equation with adiabatic (Neumann) boundary conditions. The temperature gradient over the glass fiber reinforced polymer specimen has been analyzed and validated with a commercially available three dimensional mathematical finite element model to retrieve the quantitative information regarding the subsurface defects. The efficiency of the proposed method is highlighted using matched filter based approach for a frequency modulated imposed heat flux. The depth resolvability of the proposed method has been studied from the obtained correlation lag and the time domain phase obtained for FMTWI technique.